Comparison between the Traditional and a Rapid Screening Test for Cryoimmunoglobulins Detection. (26th January 2015) - Romitelli, Federica; Pucillo, Leopoldo Paolo; Basile, Umberto; Di Stasio, Enrico
Abstract : Objectives . A new rapid, automatic, and sensitive screening test useful to detect cryoglobulins in serum samples is proposed. Design and Methods . The increase of turbidity during the cryoglobulin aggregation was monitored spectrophotometrically in sera from 400 patients with clinical evidence of cryoglobulinemia related disorders and 100 controls. Results were correlated to those obtained by the traditional method. Results . Kinetics of the aggregation curves were described by their maximum turbidity increase, lag time, and slope. Despite a partial correspondence between the traditional and the rapid test, patients with symptomatic cryoglobulinemia showed turbidity values significantly higher than the determined cutoff. Moreover, a functional classification of cryoglobulins is proposed. Conclusions . Due to its high reproducibility, operator independence, low cost, and results obtained within 2 hours, the rapid test can be used as a "real time" monitoring of cryoglobulinemia related diseases and for the evaluation of plasmapheresis efficacy.